2018
DOI: 10.1097/pcc.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Admission Hyperoxia Is a Risk Factor for Mortality in Pediatric Intensive Care*

Abstract: In this single-center study, hyperoxia at admission to the PICU was highly correlated with increased risk-adjusted mortality. Further investigation of these observations in a large multicenter cohort is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 30 publications
0
49
1
Order By: Relevance
“…The rise in mortality in the patients with greatest Pao 2 did not significantly exceed the nadir in mortality which was present in the Pao 2 188-300 torr (25.1-40.0 kPa) group. In another investigation with 1,447 patients, Numa et al (4) identified an association with rising mortality in a model incorporating an unmodified PIM-3 score. Notably, the PIM-3 score includes the F:P ratio, with the net effect that patients with higher Pao 2 would be expected to have lower PIM-3 (expected mortality) (16).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rise in mortality in the patients with greatest Pao 2 did not significantly exceed the nadir in mortality which was present in the Pao 2 188-300 torr (25.1-40.0 kPa) group. In another investigation with 1,447 patients, Numa et al (4) identified an association with rising mortality in a model incorporating an unmodified PIM-3 score. Notably, the PIM-3 score includes the F:P ratio, with the net effect that patients with higher Pao 2 would be expected to have lower PIM-3 (expected mortality) (16).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies evaluating the association between presenting hyperoxemia and mortality among critically ill children performed adjustment with uncalibrated measures of illness severity (4,8). Such severity of illness requires recalibration before application to singlecenter data (10,11).…”
mentioning
confidence: 99%
“…18,19,20,21,22 In contrast, 2 large observational studies identified an association between presenting hyperoxemia and mortality among diagnostically diverse cohorts of critically ill children. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…Expert opinion has suggested that extreme hyperoxemia may be an indirect measurement of patients undergoing brain death testing or being assessed for organ donation eligibility ( 4 ). However, as relatively few PICU patients undergo brain death testing within 24 hours of admission, the findings of our sensitivity analysis, combined with prior studies of the impact of early hyperoxemia, would suggest this is less likely ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 86%
“…Because prior work has suggested a parabolic (“U-shaped”) relationship between Pa o 2 and mortality ( 5 , 6 ), we performed a Box-Tidwell test. We developed a multivariable logistic regression model of predicted mortality, with a random effect for hospital, and plotted the expected and actual mortalities of patients grouped by differing maximum Pa o 2 values using bin widths of 100 mm Hg.…”
Section: Methodsmentioning
confidence: 99%